FISH ASSEMBLAGE STRUCTURE IN GREATER ZAB RIVER NEAR ASKI-KALAK, ERBIL - Safeen.O. S.,; S. M. A. Abdulla, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The study was conducted at the Greater Zab River at Aski-Kalak City in three stations during the period from November 2020 to October 2021.The lowest water temperature value was 9.2°C at January while the highest value was 30 °C during July 2021. Salinity values ranged between 0.21 at January to 0.49 g/l during July 2021. Dissolve oxygen was high which range between 12.5 and 5.2 mg/l during December 2020 and July 2021 respectively. A total of 2368 specimens with a total weight of 848.97Kg were collected. These fishes were represented by 28 fish species belong to 7 families.The dominance commercial fishes (15 species) were recorded with a total weight of 775.56 kg formed 91.35% of a total fish catches. While, non – commercial fishes (13 species) were recorded with a total weight of 73.41kg represent 8.65% of total fishes catches. Fish species of Chondrostoma regium were occurred to be dominating of fish number and represented by 11.9% followed by Capoeta trutta (11.8%) and Arabibarbus grypus (11.1%) of total fish caches. Also, fish species of Luciobarbus kersin come at the first of total weight of fish catches and formed 18.15%,  then followed by Arabibarbus grypus (16.12%) and Cyprinus carpio (7.95%). Finally, fishes of Alburnu spallidus formed the lowest in fish number within 0.2% and in fish total weight was Garrarufa within 0.01% of total fish catches. Thepresent study concluded that Greater Zab River within freshwater, good airing and a favorable habitat for different fish species, more of that, there was considerable stock of commercial Iraqi fishes.